The Covid-19 Pandemic and European Trade Flows: Evidence from a Dynamic Panel Model - Guglielmo Maria Caporale; Anamaria Diana Sova; Robert Sova (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the impact of the Covid-19 pandemic on trade flows in the case of the European countries. First, an ARDL dynamic panel model is estimated using the PMG method to analyse monthly data covering the most recent period (2019M1-2021M12); then, the GMM and PCSE approaches are applied to a much longer span of quarterly data (2000Q1-2021Q4), which also includes the Global Financial Crisis (GFC) of 2007-2009, in order to compare the trade impact of two different crises. The findings based on the monthly data provide clear evidence of the significant negative effects of the Covid-19 pandemic on both exports and imports in both the short and the long run, and also suggest that digitalization was instrumental in mitigating the impact of the crisis and speeding up the recovery. The quarterly analysis over a longer time period indicates that both the GCF and the Covid-19 pandemic had negative effects on trade but of a different magnitude. The use of digital technology enabling remote work and e-commerce are again some of the factors likely explaining why international trade fell by less and also rebounded much more quickly during the Covid-19 pandemic compared to the GFC.
Keywords: C25; E61; F13; F15; 330; Covid-19 pandemic; trade flows; dynamic panel models; pooled mean group (PMG) estimator